2018
DOI: 10.4111/icu.2018.59.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Can feeling of incomplete bladder emptying reflect significant postvoid residual urine? Is it reliable as a symptom solely?

Abstract: PurposeThe main objective of this study was to reveal the relationship between lower urinary tract symptoms (LUTS) and post-void residual (PVR) urine volume.Materials and MethodsBetween October 2014 and February 2015, older than 40 years patients were included in this study. Volunteers filled out a questionnaire consisted of demographic characteristics, comorbidities, medications, history of surgery and LUTS. Volunteers were undergone PVR measurement with transabdominal ultrasonography. The relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Only a few other studies to date have examined the association of SIBE and objective bladder emptying in women. A recent study by Ozlulerden et al 11 looked at 183 women presenting with LUTS. While they noted a positive correlation between SIBE and PVR volume, the average PVR volumes were still quite low (~21 ml) and likely of minimal clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few other studies to date have examined the association of SIBE and objective bladder emptying in women. A recent study by Ozlulerden et al 11 looked at 183 women presenting with LUTS. While they noted a positive correlation between SIBE and PVR volume, the average PVR volumes were still quite low (~21 ml) and likely of minimal clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In men, it may be caused by various pathologies, such as benign prostate hyperplasia, bladder outlet obstruction, urethral or meatal stricture, underactive bladder, and neurogenic bladder [17]. The PVR volume significantly affects the quality of life due to the fact that increased PVR may reduce functional bladder capacity and cause symptoms of the lower urinary tract [21]. Current studies have shown that it is associated with many complications ranging from a simple lower urinary tract symptom to acute and chronic renal failure [24].…”
Section: Discussionmentioning
confidence: 99%
“…49 Conflicting results have been published on the relationship between the sensation of incomplete voiding and post-voiding residual. 50,51 In addition, the lower urinary tract can distinguish between hot and cold, but this has received little research attention. Nociceptive sensation as pain and the mechanical movement associated with catheters or endoscopes generate sensory information; however, this is not used in sensory evaluation.…”
Section: Other Sensation Evaluationmentioning
confidence: 99%
“…Healthy young men have reported feeling passage of urine through the urethra . Conflicting results have been published on the relationship between the sensation of incomplete voiding and post‐voiding residual . In addition, the lower urinary tract can distinguish between hot and cold, but this has received little research attention.…”
Section: Clinical Investigation Of Bladder Sensationmentioning
confidence: 99%